Dispute boards procedures and practice - Owen, Gwyn 1951- (Thomas Telford, 2007)
This book outlines the various contract procedures which require or permit the use of Dispute Boards. It gives a detailed explanation of interpretation and application of each requirement, both practical and legal/contractual, referring to the international Conditions of Contract published by FIDIC.